Stochastic Simulation of the Cell Cycle Model for Budding Yeast (Communications in Computational Physics, 2018)
We use the recently proposed Nested Stochastic Simulation Algorithm(Nested SSA) to simulate the cell cycle model for budding yeast. The results showthat Nested SSA is able to significantly reduce the computational cost while capturingthe essential dynamical features of the system.